Epidemiologic Factors and Urogenital Infections Associated With Preterm Birth in a Midwestern U.S. Population - Agger, William A. (Obstet Gynecol, 2014)
OBJECTIVE: To correlate epidemiologic factors with urogenital infections associated with preterm birth. METHODS: Pregnant women were sequentially included from four Wisconsin cohorts: large urban, midsize urban, small city, and rural city. Demographic, clinical, and current pregnancy data were collected. Cervical and urine specimens were analyzed by microscopy, culture, and polymerase chain reaction for potential pathogens. RESULTS: Six hundred seventy-six women were evaluated. Fifty-four (8.0%) had preterm birth: 12.1% (19/157) large urban, 8.8% (15/170) midsize urban, 9.4% (16/171) small city, and 2.3% (4/178) rural city. Associated host factors and infections varied significantly among sites. Urogenital infection rates, especially Mycoplasma hominis and Ureaplasma parvum, were highest at the large urban site. Large urban site, minority ethnicity, multiple infections, and certain historical factors were associated with preterm birth by univariable analysis. By multivariable analysis, preterm birth was associated with prior preterm birth (adjusted odds ratio [aOR] 2.76, 95% confidence interval [CI] 1.27–6.02) and urinary tract infection (aOR 2.62, 95% CI 1.32–519), and negatively associated with provider-assessed good health (aOR 0.42, 95% CI 0.23–0.76) and group B streptococcal infection treatment (surrogate for healthcare utilization) (aOR 0.38, 95% CI 0.15–.99). Risk and protective factors were similar for women with birth at < 35 weeks, and additionally associated with M hominis (aOR 3.6, 95% CI 1.4–9.7). CONCLUSION: These measured differences between sites are consistent with observations that link epidemiologic factors, both environmental and genetic, with minimally pathogenic vaginal bacteria, inducing preterm birth, especially at less than 35 weeks of gestation.